Ressignificando a atuação da supervisão pedagógica na Educação Básica - Angelita Hentges (Universidade Federal de Rondônia, 2017)
The reflections in this text has as base the research of the Master in Education entitled: "School Supervision: possibilities of resignification", which aimed to analyze the role of the school/pedagogical supervisor, regarding the need to implement continuing education processes in basic education school. It developed through participant research methodology, happening with the involvement of different public school teachers who played the role of pedagogical supervisors. The analysis of the investigation demonstrated possibilities of resignification of conception of the action of this professional through organization and experience of continuing education spaces of teachers in the school, lined by presuppositions of communicative interaction, dialogue and otherness.